Influences of inflow rates on the breach characteristics of landslide dams - Jiang, Xiangang; Zhang, Zongliang; Deng, Hongyan (Frontiers in Earth Science, 2024)
IntroductionDams formed by landslides may produce disastrous floods after dam outbursts. However, understanding of the influence of the inflow rate on the breaching characteristics of landslide dams is still at an early stage; in particular, the relationship between breaching width and depth are still unclear.MethodsIn this paper, we present the results of a series of laboratory tests that assessed seven inflow rates (1, 1.5, 2, 2.5, 3, 3.5, and 4 L/s).Results and discussionThe results show that breaching characteristics for different inflow rates are similar and that there are three breach stages for different inflow rates. The peak discharge gradually increases as the inflow rate increases. With increasing inflow rate, the breach depth and width both increase. The ratio of breach width to breach depth increases from less than 1 to 1 progressively with increasing inflow rate. The breaching width and depth can be expressed by the function W=ζ1+e−kD−D0. The shape parameter k has an exponential relationship with the inflow rate.